The Concepts of Sāstratah, Gurutah, and Swatah in Strengthening Magnanimous Character as A Preventive Strategy Against The Phenomenon of Suicide in Bali - I Putu Suyasa Ariputra; Encep Syarief Nurdin; Yadi Ruyadi; Kadek Aria Prima Dewi PF; Juntika Nurihsan; Bunyamin Maftuh; Ace Suryadi; Asep Dahliyana; Warlim Warlim (Jayapangus Press, 2026)
The phenomenon of suicide in Bali shows an increasing trend that raises a socio-religious paradox amid the strong traditional structures and Hindu spirituality. Various studies confirm that depression, psychosocial pressure, low self-regulation, and loss of meaning in life contribute significantly to the emergence of suicidal ideation. This study aims to analyse the strengthening of character through the concepts of Sāstratah, Gurutah, and Swatah as Hindu psychospiritual-based preventive strategies. The study uses a qualitative approach, grounded in a literature review, through critical analysis of scriptures, Hindu theological literature, and relevant psychological and mental health studies. The results of the study show that Sāstratah lays the foundation for meaning in life by understanding humans as atman, with a dharma-and mokṣa-oriented perspective. Gurutah presents a process of inner clarification through reflective dialogue and guided yoga practices that strengthen emotional regulation and self-awareness. Swatah marks the deepest stage of internalisation, when yajña transforms from an external ritual into an internal burning of the ego, giving birth to compassion and existential resilience. The magnanimous character formed through these three paths functions as a psychospiritual fortress that strengthens the meaning of life, self-control, and resilience to pressure. The scientific contribution of this article lies in the formulation of a tiered psychospiritual model that integrates classical Hindu texts with modern psychological theory as a contextual conceptual reinterpretation for Balinese society. This study is theoretical and literature-based, thus requiring further empirical research to test the model's validity and effectiveness in measurable terms. Thus, the concepts of Sāstratah, Gurutah, and Swatah contribute as a conceptual framework for Hindu-based character education in contextual and transformative preventive efforts to reduce suicidal ideation.